2022
DOI: 10.1002/fsn3.3121
|View full text |Cite
|
Sign up to set email alerts
|

Reducing salt intake with umami: A secondary analysis of data in the UK National Diet and Nutrition Survey

Abstract: Reducing sodium content in foods is an important public health measure to reduce salt intake and decrease the incidence of noncommunicable diseases, such as cardiovascular disease and chronic kidney disease. This study quantified the amount of salt intake that could potentially be reduced by using umami substances, including glutamate, inosinate, and guanylate, without compromising taste, for adults in the United Kingdom (UK). We used data comprised of 1834 adults aged 20 years and over from the National Diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Purine nucleotides are also umami components. Using nucleotide umami substances, such as guanosine 5'-monophosphate and inosine 5'-monophosphate, in combination with monosodium glutamate, has been reported to reduce salt intake without impairing taste [40]. Furthermore, the intestinal epithelium has a high demand for nucleotides for energy acquisition, proliferation, and innate immunity, and the significant increase in nucleotide substrate requirement during injury, infection, and wound healing is well known.…”
Section: Dietmentioning
confidence: 99%
“…Purine nucleotides are also umami components. Using nucleotide umami substances, such as guanosine 5'-monophosphate and inosine 5'-monophosphate, in combination with monosodium glutamate, has been reported to reduce salt intake without impairing taste [40]. Furthermore, the intestinal epithelium has a high demand for nucleotides for energy acquisition, proliferation, and innate immunity, and the significant increase in nucleotide substrate requirement during injury, infection, and wound healing is well known.…”
Section: Dietmentioning
confidence: 99%
“…Some studies showed that umami substances can be used as a substitute for salt, which may be able to help people reduce their salt intake thereby decreasing the risk of people suffering from non-communicable diseases (NCD), such as cardiovascular disease, chronic kidney disease, and stomach cancer. 1,2 The substances that can exert umami flavor contain nucleotides, free amino acids, peptides, organic acid, and their derivatives, 3 and among which umami peptides have attracted a great deal of interest from food-related scientists and entrepreneurs as a consequence of their natural and valuable features.…”
Section: Introductionmentioning
confidence: 99%